Skin-close computing and wearable technology : a key to enthusiastic researchers with human-centric approach - Samraj, Andrews (Boca Raton, FL : CRC Press, 2022)
"This book is aimed at senior undergraduate, graduate students and researchers in biomedical engineering, bioinstrumentation, biosensors, and assistive technology"--
Basic wearable computing requirements and advantages -- Ergonomics and its benefits -- Applications of wearable technology -- Simple user interface design for wearable computing and wearable technology -- Materials and components (constructing a simple wearable technology device) -- Assistive technology and WT -- Security technology and WT -- In simulator assessment of a feedforward visual interface to reduce fuel use -- Software and power requirements of WT -- Human interface and robotic interface -- Soft cyborgs and cyber physical systems by WT.
OCLC-licensed vendor bibliographic record.
Keywords: Wearable computers; Wearable technology; Self-help devices for people with disabilities; COMPUTERS / Computer Engineering; COMPUTERS / Social Aspects / Human-Computer Interaction; TECHNOLOGY / Electricity